2020
DOI: 10.1128/msystems.00609-19
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Cluster That Encodes Histone Deacetylase Inhibitors Contributes to Bacterial Persistence and Antibiotic Tolerance in Burkholderia thailandensis

Abstract: Persister cells are genetically identical variants in a bacterial population that have phenotypically modified their physiology to survive environmental stress. In bacterial pathogens, persisters are able to survive antibiotic treatment and reinfect patients in a frustrating cycle of chronic infection. To better define core persistence mechanisms for therapeutics development, we performed transcriptomics analyses of Burkholderia thailandensis populations enriched for persisters via three methods: flow sorting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 78 publications
2
12
0
Order By: Relevance
“…We further investigated tRA99020 dosage effect on the activation of a gene associated with antibiotic tolerance in B. thailandensis persister cells. In our previous study, using comparative transcriptomics and functional genomic assays, we have demonstrated that polyketide synthase (PKS) function played a significant role in B. thailandensis persistence to a variety of antibiotics [ 10 ]. Here, we utilized the pks gene expression as a biomarker of persistence onset.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We further investigated tRA99020 dosage effect on the activation of a gene associated with antibiotic tolerance in B. thailandensis persister cells. In our previous study, using comparative transcriptomics and functional genomic assays, we have demonstrated that polyketide synthase (PKS) function played a significant role in B. thailandensis persistence to a variety of antibiotics [ 10 ]. Here, we utilized the pks gene expression as a biomarker of persistence onset.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that polyketide metabolites produced by B. thailandensis PKS systems act as inhibitors of mammalian histone deacetylase (HDACi) enzymes in in vitro assays [ 10 ]. Since HDAC activity in mammalian cells is essential for rapid immune responses to infections [ 31 , 32 ], we tasked ourselves with testing the efficacy of B .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations